Cutting a Gordian knot? Understanding the relationship between culture and process, environment, and people in military planning. - English, N G (Cranfield University, 2021)
Military planning is designed to make sense of rapidly changing, dangerous and stressful environments and generate activity that influences an adversary’s behaviour against their will. This thesis explores the experience of military planning and why some practitioners appear to find structured planning processes difficult to use in practice. A review of military specific literature revealed that the human experience of military planning is relatively underdeveloped in comparison to other more technically focussed areas. This thesis addresses that gap through a comprehensive analysis of planning and decision-making research. Using a critical realist research design, it exposes a rich, multi-disciplinary body of knowledge to develop a transferable theoretical framework. A thematic analysis of culture and process, environment, and people then forms the foundation for a revelatory case study of real-world planning conducted in Afghanistan in 2014. This thesis argues that practitioners find structured planning difficult because, under certain conditions, their expectations and contextual understanding become dislocated from their environment. It proposes that this sense of dissonance is grounded in the inter-relationship between socio-cultural norms and expectations, naturalistic behaviour, and perception of the environment. Rather than an isolated phenomenon, it suggests that dissonance acts as the trigger for adaptation and as an indicator of impending instability and fragility particularly when relative complexity is high. In many ways, planning practice resembles a complex adaptive reflexive system; it adapts not only in response to the environment and the problem faced but also to the emotional experience of the practitioners within it. Finally, it recommends a number of potential strategies to increase the stability and robustness in military planning under a wider range of environmental conditions than is currently possible.
© Crown Copyright 2021. All rights reserved. No part of this publication may be reproduced without the written permission of the copyright owner.
Keywords: Wicked problems; Military planning; Decision making